2020
DOI: 10.1371/journal.pone.0229961
|View full text |Cite
|
Sign up to set email alerts
|

Spatial index relating urban environment to health lifestyle and obesity risk in men and women from different age groups

Abstract: The challenge in the search for relationships between urban space, physical mobility, and health status, is detecting indicators able to link the environment with healthy life habits. Therefore, the objective was to design an urban index for the identification of urban environment propensity for physical activity (PA) and to determine how it relates to lifestyle and anthropometric parametrization of obesity. Participants (N = 318-60.4% women and 39.6% men) were recruited from a mid-sized city with epidemiology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
0
4
0
3
Order By: Relevance
“…Thus, our findings of a lower obesity risk associated with contexts with greater SCCR in young people could be related to a mechanism mediated by the availability, perception and use of sports centres or other amenities that were part of the SCRR index. In a Brazilian study on obesity, the authors reinforce the idea that a favourable decrease in 'obesogenic' traits in the urban environment is possible when physical structures are planned to facilitate physical activity (50) . Alternatively, we propose that the distribution of the SCRR variable could depict a sort of 'regionalisation' (geographical division) underlying socio-economic and cultural characteristics of the populations or could represent different patterns of land use.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Thus, our findings of a lower obesity risk associated with contexts with greater SCCR in young people could be related to a mechanism mediated by the availability, perception and use of sports centres or other amenities that were part of the SCRR index. In a Brazilian study on obesity, the authors reinforce the idea that a favourable decrease in 'obesogenic' traits in the urban environment is possible when physical structures are planned to facilitate physical activity (50) . Alternatively, we propose that the distribution of the SCRR variable could depict a sort of 'regionalisation' (geographical division) underlying socio-economic and cultural characteristics of the populations or could represent different patterns of land use.…”
Section: Discussionmentioning
confidence: 80%
“…These results may reflect poor access to a healthy diet and low opportunities to adopt healthy behaviours, in women with a low-income level, especially if they live in urbanised areas. Interestingly, Oliveira et al (50) indicated that there are several aspects (physical, economic, political and sociocultural) of the environmental factors that would independently affect men and women, and that obesogenic influence of the environment may differ in small and medium-sized cities, when compared to large cities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Серед здорових звичок його мешканців фіксували некуріння (~94 %) і невживання алкоголю (~55 %). Виявилося, що міське середовище цілком здатне сприяти здоровим звичкам незалежно від статі і вікової групи (Oliveira et al, 2020).…”
Section: субкультура пізньої зрілостіunclassified
“…Historical, political, physical, economic, and social environments not explored by this study might be capable of impacting PA, given that they independently impact environmental associations with PA in the different countries. 7,36,69 For example, Brazil has a different urban planning and design approach from those of other countries in the region. Argentina, Colombia, Ecuador, Peru, and Venezuela were mainly colonized by Spain; therefore, their urban morphology is different from that of Brazil, which was colonized by Portugal.…”
Section: Article In Pressmentioning
confidence: 99%